Managing front office operations - Kasavana, Michael L (American Hotel & Lodging Association, Educational Institute, 2015)
"This ... textbook provides students with an in-depth look at management of the front office and how this department interacts with other hotel departments to create a memorable guest experience. The eighth edition been revised with new material on the potential impact of automated information technologies on a variety of front office functions. This edition also includes new information on revenue managers, how blogging and social networking affect hotels, manual backup procedures for automated system failure, identity theft prevention, payment card security standards, and green hotels. In addition, important discussions of front office operations have been expanded throughout the text, especially with respect to human resources management, business forecasting, revenue management, budget planning, and front office staff interaction with sales, housekeeping, and security personnel."